Analysis of the contributing factors for fatal accidents due to falls from heights in Malaysia and the USA - Zermane, Abderrahim; Mohd Tohir, Mohd Zahirasri; Baharudin, Mohd Rafee; Mohamed Yusoff, Hamdan (Universiti Putra Malaysia Press, 2020)
Working at heights has always been a concern for the process industry and construction industry. According to recent statistics, falls from heights are the leading cause for at least a third of all construction accidents, based on the accident reports from Malaysia, United States of America (USA) and Great Britain. Therefore, the aim of this research is to investigate the contributing factors for fatal accidents due to falls from heights based on published official data by government agencies such as Department of Occupational Safety and Health (DOSH) in Malaysia and Occupational Safety and Health and Administration (OSHA) in the USA. Thorough risk analysis of accidents due to falls from heights is needed as a step to improve the safety of workers and reduce the number of fatalities. The methodology used was developed through an in-depth literature review from relevant publications that discussed falls from heights investigations ranging from individual characters to management commitment and site conditions. The data is available and accessible to the public via OSHA and DOSH and can be obtained by browsing their websites. The data were analysed based on the relevant understanding of the description mentioned in the accident reports and its relationship with the contributing factors. Eventually, from the analysis, the factors which affect more the numbers of fatal accidents due to falls from heights were obtained. In this study, 105 fatal accidents due to falls from heights from Malaysia data and 101 fatal accidents from USA data were selected through a precise selecting process and analysed to determine which factor was the highest contributor to increasing the number of fatal workplace accidents due to falls from heights. Results indicate that a lack of effective management is the highest contributor to falls from height fatal accidents.